PENGUATAN HUKUM ADAT DALAM POLITIK HUKUM NASIONAL (Integrasi untuk Penguatan Pluralisme Hukum) - Mamnun, M. Khairu; Viutari, Aulia Iqlima (Faculty of Law, Universitas Tanjungpura, 2025)
Abstract Customary law is a legal system that has lived and developed from generation to generation in Indonesian society, reflecting local values and becoming an integral part of the nation's cultural identity. However, in practice, customary law is often marginalized by the dominance of the formal and legalistic national legal system. This article aims to analyze efforts to integrate customary law into national legal politics through the approach of legal pluralism theory. This theory emphasizes the importance of recognizing the diversity of legal systems that coexist in one social space, without a hierarchy that places state law above other laws. The research was conducted using qualitative methods with a legislative and conceptual approach, which was examined descriptively-analytically. The results of the study show that although the constitution and a number of laws and regulations have recognized the existence of customary law, its implementation is still weak due to the lack of structural protection and partisanship in national legal policy. Effective integration of customary law requires structural reform, harmonization of legislation, strengthening of customary institutions, and contextual legal education. In addition, this article highlights the importance of the transition from weak legal pluralism to strong legal pluralism, where customary law is treated equally with state law. By adopting a legal pluralism approach, Indonesia has the potential to build an inclusive and socially just legal system, as well as strengthen the protection of indigenous peoples' rights as part of a sustainable national legal development strategy rooted in the nation's socio-cultural realities. Abstrak Hukum adat merupakan sistem hukum yang telah hidup dan berkembang secara turun-temurun dalam masyarakat Indonesia, mencerminkan nilai-nilai lokal serta menjadi bagian integral dari identitas budaya bangsa. Namun, dalam praktiknya, hukum adat sering kali termarjinalkan oleh dominasi sistem hukum nasional yang bersifat formal dan legalistik. Artikel ini bertujuan untuk menganalisis upaya integrasi hukum adat ke dalam politik hukum nasional melalui pendekatan teori pluralisme hukum. Teori ini menekankan pentingnya pengakuan terhadap keberagaman sistem hukum yang hidup berdampingan dalam satu ruang sosial, tanpa hierarki yang menempatkan hukum negara di atas hukum lainnya. Penelitian dilakukan menggunakan metode kualitatif dengan pendekatan perundang-undangan dan konseptual, yang dikaji secara deskriptif-analitik. Hasil kajian menunjukkan bahwa meskipun konstitusi dan sejumlah peraturan perundang-undangan telah mengakui eksistensi hukum adat, implementasinya masih lemah akibat minimnya perlindungan struktural dan keberpihakan dalam kebijakan politik hukum nasional. Integrasi hukum adat yang efektif membutuhkan reformasi struktural, harmonisasi legislasi, penguatan lembaga adat, dan pendidikan hukum yang kontekstual. Selain itu, artikel ini menyoroti pentingnya transisi dari weak legal pluralism menuju strong legal pluralism, di mana hukum adat diperlakukan secara setara dengan hukum negara. Dengan mengadopsi pendekatan pluralisme hukum, Indonesia berpotensi membangun sistem hukum yang inklusif dan berkeadilan sosial, serta memperkuat perlindungan hak masyarakat adat sebagai bagian dari strategi pembangunan hukum nasional yang berkelanjutan dan berakar pada realitas sosial budaya bangsa.